Urinary tract infections and antibiotic susceptibility among the patients attending B & D hospital of Lalitpur, Nepal - Joshi, Yadav Prasad; Shrestha, Shreejeet; Kabir, Russell; Thapa, Anita; Upreti, Parbati; Shrestha, Sanjit (Asian Journal of Medical Sciences, 2016)
Background: Urinary tract infection is the most common bacterial infections in humans and serious health problem in many parts of the world. It has become more complicated in treatment due to different pathogens and increasing resistant to antimicrobial agents. This study aims to investigate the prevalence of urinary tract infection and antibiotic susceptibility patterns of pathogens among the patients attending in B & B hospital Nepal. Materials and Methods: A hospital based cross sectional study was conducted in between April 2010 to March 2011. Urine samples were collected from clinically suspected patients and tested bacteriologically using standard procedures. Antimicrobial susceptibility test was performed for isolated pathogen using the Kirby-Bauer disk diffusion method according to Clinical and Laboratory Standards Institute guidelines. Results: Out of 1260 examined specimens 25.24 % were positive and majority 61.64% were females. The most common pathogens isolated were Escherichia coli (66.67%), Enterococcus (7.55%) and Staphylococcus (6.60 %). The drug resistant among the positive cases were reported. The highest resistant of positive cases was found with Cefexime (87.88%) and Enterococcus with Ampicillin (66.67%) and Staphyllococcus with Cloxacillin (66.67%). The highest susceptibility was for Vancomycin and Ampicillin i.e. 33.33% in each. Conclusion: The findings showed that E. coli isolates were the predominant pathogen and the presence of bacterial isolates with very high resistance to the commonly prescribed drugs. As drug resistance among bacterial pathogens is an evolving process and serious issue. Therefore, routine surveillance and monitoring studies should be conducted to provide physicians knowledge on the updated and most effective empirical treatment of UTIs. Asian Journal of Medical Sciences Vol.7(5) 2016 47-51